Pemberdayaan Masyarakat Melalui Partisipasi Masyarakat Dalam Kegiatan Program Budidaya Tanaman Sayur Mayur Sehat di Kampung Tematik Kota Bengkulu - Citra, citra; Agusmi H, Pety; Gusti, Ririn (JPUS: Jurnal Pendidikan Untuk Semua, 2022)
Participation cannot be separated from people's lives where suggestions, ideas and ideas from the community are needed in the community development sector itself. Community participation in the decision-making process is a direct involvement of the community in the development planning process. The purpose of this study is to find out how community empowerment activities are carried out through community participation in thematic villages, the method used is qualitative which is presented descriptively. The results showed that the success of empowering the community to participate in the development of thematic villages such as giving ideas, ideas or what can be called thoughts then participating in the form of energy with the community participating in activities such as mutual cooperation for the management of healthy vegetable plantations, participating in the form of community property voluntarily spending money and community participation skills and proficiency. Supervision is carried out such as the selection of vegetable seeds, the planting process to supervision until they are marketed. The factors contained in the community empowerment program through community participation in thematic villages such as environmental conditions and resource factors.